Penerapan manajemen risiko hukum dalam perbankan syariah: Prespektif terkini terhadap regulasi dan teknologi - HANIFATURASYDA, ARFINA (Maliki Interdisciplinary Journal, 2025)
This article talks about how Islamic banks manage legal risks, especially with the changes happening in rules and technology. Islamic banking faces special challenges because it must follow not only national laws but also Islamic (sharia) principles. The study uses information from books, journals, and official regulations from institutions like Bank Indonesia and the Financial Services Authority (OJK). The article explains how legal risk management helps prevent problems, ensures the bank follows the rules, and improves how the bank is run. It also shows how technology, like digital services and automated legal documents, can help make legal risk management stronger. The study finds that combining flexible rules with the right technology can reduce legal risks and make Islamic banks work more efficiently. To face future challenges, Islamic banks need smart and technology-based strategies to manage legal risks better.